Retinoblastoma research trends from 1980 to 2023: a 44-year bibliometric study - Yun Zhao; Yining Wang; Yuchuan Wang; Yuchuan Wang; Yuchuan Wang; Jiagen Li; Jiagen Li; Hongxun Li; Hongxun Li; Hong Zhao; Hong Zhao; Hong Zhao; et al. (Frontiers in Oncology)
BackgroundRetinoblastoma (RB) is the most common intraocular malignant tumor in children. It not only seriously threatens patients’ vision but also endangers their lives if not treated in time. Our objective is to analyze research trends in the RB field and compare contributions from different countries, institutions and authors.MethodsWe extracted all RB-related publications published from 1980 to 2023 from the Web of Science database and applied VOSviewer, R software, Bibliometrix software, Origin 2024 and CiteSpace to review the publication data, analyze the publication trends, and visualize the relevant data. In this study, the research papers on RB published in the past 44 years were classified by year, country/region, institution/university, journal, author and keywords to reveal the research hotspots and development trends in this field.ResultsA total of 4156 papers on RB were identified from 1980 to 2023. In 1980, only 13 papers were published, yet by 2023, 237 papers had been published. These publications were contributed by 351 research institutes from 68 countries/regions. The United States ranked first with 1662 papers, accounting for 39.99% of the total number of publications on RB research. A total of 539 RB research papers were published in China, ranking second. India, Canada and Germany ranked third, fourth and fifth, with 377, 277 and 221 publications, respectively. Thomas Jefferson University published the most research papers on RB, with 166 published papers, accounting for 3.99% of all publications. The top three journals contributing to this field were Invest Ophth Vis Sci, the British Journal of Ophthalmology and Ophthalmology. Liquid biopsy, intra-arterial chemotherapy and intravitreal chemotherapy are the most frequently used keywords in the field.ConclusionOver the past 44 years, the United States, China, India, Canada and Germany have led the field of research on RB. Many renowned research institutions and ophthalmologists have made important contributions to RB research and will continue to lead this research direction. Liquid biopsy, intra-arterial chemotherapy and intravitreal chemotherapy are potential hotspots for RB research in the future.